Indonesia’s Electronic Information and Transactions Law: History, Impact, and Challenges - Adisti Puspa Setyawan; Antonius Sambodo Adi A; I Dewa BS Wirantaya; Pina Mustika; William Gomarga (Publikasi Indonesia, 2025)
This paper examines the history, impact, and challenges of Indonesia's Electronic Information and Transactions Law (Law No. 11 of 2008, as amended by Law No. 19 of 2016) through a descriptive qualitative approach. By conducting a systematic content analysis of primary legal texts, official ministry reports, and secondary scholarly literature, the study reconstructs the law's evolutionary trajectory from its initial focus on electronic signatures and contract validity to the expanded criminalization of digital offenses, including defamation, hate speech, and data misuse. The analysis is conducted using Miles and Huberman’s coding technique to identify patterns related to regulatory developments, socio-economic impacts, and associated challenges. The research finding indicate that reveal that the ITE Law has enhanced digital governance in libraries by curbing misinformation and protecting intellectual property, strengthened consumer protection in online commerce by clarifying rights and dispute mechanisms, and initiated regulatory frameworks for emerging fintech platforms. Despite these positive developments, the research identifies persistent implementation challenges, including socio-cultural resistance, legal ambiguities, resource constraints, and the rapid pace of technological change, that hinder consistent enforcement across regions. The paper concludes by recommending targeted legal literacy campaigns, more explicit legislative provisions, and agile regulatory review mechanisms to ensure the continued relevance and effectiveness of the ITE Law in striking a balance between innovation, fundamental rights, and national stability.